Thermodynamically Spontaneous Reactions and Use of Acetaldehyde as Fuel in Direct Ethanol Fuel Cells - Yasuro Ikuma; Koichi Niwa; Tetsuya Imamura (ECS Advances, 2023)
A set of fuel cells was fabricated using a cation exchange membrane (CEM), and ethanol and acetaldehyde were used as fuels for the cells. Spontaneous reactions in the fuel cells were studied under various conditions such as excess oxygen at the cathode and at higher temperatures without application of an external voltage and without forcing an external current. When acetaldehyde was used as a fuel, the current in the circuit and the concentration of acetic acid (product of the fuel cells) were not influenced by the experimental conditions. On the other hand, when ethanol was used as a fuel, the current in the circuit and the concentration of acetic acid were influenced by the experimental conditions. It was thus concluded that ethanol is oxidized directly to acetic acid without oxidation to acetaldehyde and then to acetic acid. The calculated Δ G for possible half reactions in direct ethanol fuel cells (DEFCs) with CEM and AEM (anion exchange membrane) suggests that a reliable AEM should be developed for the further development of DEFCs.